The impact of pre-existing chronic heart failure on the intensive care treatment and outcome of old intensive care patients suffering from COVID-19. (3rd October 2022) - Bruno, R R; Wernly, B; Wolff, G; Artigas, A; Pinto, B B; Schefold, J C; Kindgen-Milles, D; Baldia, P H; Kelm, M; Beil, M; Leaver, S; De Lange, D W; et al.
Abstract: Background: Patients suffering from COVID-19 with pre-existing chronic heart failure (CHF) are considered to have a significant risk regarding morbidity and mortality. Similarly, older patients on the intensive care unit (ICU) constitute another vulnerable subgroup. This study investigated the association between pre-existing CHF and clinical practice in critically ill older ICU patients with COVID-19. Methods: Patients with severe COVID-19 and who were ≥70 years old were recruited from this prospective multicenter international study. Patients' treatment, follow-up, and pre-existing heart failure data were collected during ICU stay. Univariate and multivariate logistic regression analyses examined the association between pre-existing heart failure and the primary endpoint of 30-day mortality. Results: The study included 3, 917 patients, with 407 patients (17%) evidencing pre-existing CHF. These patients were older (77±5 versus 76±5, p<0.001) and more frail (Clinical Frailty Scale 4±2 versus 3±2, p<0.0001). The other comorbidities were also significantly more common in CHF patients. Before hospital admission, CHF patients suffered fewer days from symptoms (5 days (3–8) versus 7 days (4–10), p<0.001), but there was no difference in the days in the hospital before ICU admission (2 days (1–5) versus 2 (1–5) days, p=0.21). At ICU admission, disease severity assessed by SOFA scores was significantly higher in CHF patients (7±3 versus 5±3). During ICU-stay, intubation, mechanical ventilation, and tracheostomy occurred significantly more often in patients without CHF (63% versus 69%, p=0.017; and 13% versus 18%, p=0.002, respectively). In contrast, there was no difference regarding non-invasive ventilation (28% versus 27%, p=0.20), and the need for vasoactive drugs (66% versus 64, p=0.30). Regarding the limitation of life-sustaining therapy, therapy was significantly more often withheld (32% versus 25%, p=0.001) but not withdrawn (18% versus 17%, p=0.21) in CHF patients. Length of ICU stay was significantly shorter in CHF patients (166 (72–336) hours versus 260 hours (120–528), p<0.001). CHF patients had significantly higher ICU- (52% versus 46%, p=0.007), 30-day mortality (60% vs. 48%, p<0.001; OR 1.87, 95% CI 1.5–2.3) and 3-month mortality (69% vs. 56%, p<0.001). In the univariate regression analysis, having pre-existing CHF was significantly associated with 30-day mortality (OR 1.89, 95% CI 1.5–2.3; p<0.001), but after adjusting for confounders (SOFA, age, gender, frailty), heart failure was not independently associated any more (aOR 1.2, 95% CI 0.5–1.5; p=0.137). Conclusion: In critically ill old COVID-19 patients, pre-existing chronic heart failure is associated with significantly increased short- and long-term mortality, but heart failure is not independently associated with increased 30-day mortality when adjusted for confounders. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): This study was endorsed by the ESICM. Free support for running the electronic database and was granted from the dep. of Epidemiology, University of Aarhus, Denmark. The support of the study in France by a grant from "Fondation Assistance Publique-Hôpitaux de Paris pour la recherche" is greatly appreciated. In Norway, the study was supported by a grant from the Health Region West. In addition, the study was supported by a grant from the European Open Science Cloud (EOSC). EOSCsecretariat.eu has received funding from the European Union's Horizon Programme call H2020-INFRAEOSC-05-2018-2019, grant agreement number 831644. This work was supported by the Forschungskommission of the Medical Faculty of the Heinrich-Heine-University Düsseldorf, No. 2018-32 to GW and No. 2020-21 to RRB for a Clinician Scientist Track.